Advanced control scheme of a unifiedpower flow controller using sliding mode control - Abdellatif Hinda; Mounir Khiat; Zinelaabidine Boudjema (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper presents an advanced control scheme based on sliding mode control of a unified power flow controller (UPFC). This controller can generate a number of benefits in terms of static and dynamic operation of the power system such as the control law is synthesized with two kinds of controllers: sliding mode controller (SMC), and proportional integral (PI). Their respective performances are compared in terms of reference monitoring, sensitivity to disturbances and robustness. We have to study the problem of controlling power in electric system by UPFC. The simulation results show the effectiveness of the proposed strategy especially in chattering-free behavior, response to sudden load variations and robustness. All the simulations for the above work have been carried out using MATLAB/Simulink. Various simulations have given very satisfactory results and we have successfully improved the active and reactive power flows on a line of transmission, as well as to control voltage at the bus where it is connected, the studies and illustrate the effectiveness and capability of UPFC in improving power.